2020
DOI: 10.1515/chem-2020-0500
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium (Cd) chloride affects the nutrient uptake and Cd-resistant bacterium reduces the adsorption of Cd in muskmelon plants

Abstract: AbstractThis study investigated the effect of cadmium (Cd) chloride on the uptake of N, P, and K and evaluate the effect of Cd-resistant bacterium “N3” on reducing the adverse effect of Cd in grafted and nongrafted plants. The shoot and total dry weights of the nongrafted muskmelon plants decreased under 50 and 100 µM Cd treatments. The scion and shoot dry weights of the grafted plants increased significantly, whereas their root dry weight increased by nearly onefold compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…In the treatment of Cd+Soil, morphological traits such as root length, shoot length, shoot fresh weight, shoot dry weight and total fruit weight per plant were significantly reduced compared with control, while these traits under Cd+Soil+Oak 114 treatment decreased slightly. Similar results was found in tomato by (Djebali et al, 2005;Dong et al, 2005;Cherian et al, 2007;Gratão et al, 2008;Rehman et al, 2011;Al Khateeb and Al-Qwasemeh, 2014;Piotto et al, 2018) and in musk melon (Zhang et al, 2020). Root fresh weight, root dry weight and total chlorophyll content were increased in both Cd treatments, which was similar to results from a previous study (Rehman et al, 2011).…”
Section: Heavy Metal (Cd) Stresssupporting
confidence: 90%
See 1 more Smart Citation
“…In the treatment of Cd+Soil, morphological traits such as root length, shoot length, shoot fresh weight, shoot dry weight and total fruit weight per plant were significantly reduced compared with control, while these traits under Cd+Soil+Oak 114 treatment decreased slightly. Similar results was found in tomato by (Djebali et al, 2005;Dong et al, 2005;Cherian et al, 2007;Gratão et al, 2008;Rehman et al, 2011;Al Khateeb and Al-Qwasemeh, 2014;Piotto et al, 2018) and in musk melon (Zhang et al, 2020). Root fresh weight, root dry weight and total chlorophyll content were increased in both Cd treatments, which was similar to results from a previous study (Rehman et al, 2011).…”
Section: Heavy Metal (Cd) Stresssupporting
confidence: 90%
“…Prolonged stress, however, may induce ROS aggregation at the plasma membrane, and resultant damage to cells. Therefore, to minimize ROS generation, the plant needs the upregulation of antioxidant/detoxifying systems including APX, SOD, CAT, and POD (Barna et al, 2003;Zhang et al, 2020).…”
Section: Drought Stressmentioning
confidence: 99%
“…Macronutrients are required for the normal growth and biochemical processes of plants. Heavy metals, at elevated concentrations, inhibit the uptake and transport of essential nutrients [18][19][20]. Cadmium influences membrane permeability and decreases H + -ATPase activity, leading to a reduction in nutrient uptake [60].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated cadmium quantities in plants delay seed germination, induce growth inhibition, and reduce productivity [14][15][16]. It plays an influential role in the uptake, transport, and distribution of nutrients [17][18][19][20]. Its destructive role in the photosynthetic apparatus has been highlighted, where it reduces pigment contents [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, corresponding phosphorus contents were reduced with increasing of Cd level treatment. It was found that The N, P, and K contents in plants decreased after the addition of Cd (Zhang et al, 2020) due to the impacts of Cd on nutrient uptake. Moreover, Zafar-ul-Hye et al (2020) demonstrated that low uptake of nutrients in the presence of cadmium is a well-documented fact due to its antagonistic relationship with macronutrients.…”
Section: N P K and CD Contentsmentioning
confidence: 99%